Rupture process of the 2014 Orkney earthquake, South Africa - Makoto, Okubo; Cichowicz, Artur; Ogasawara, Hiroshi; Murakami, Osamu; Horiuchi, Shigeki (Vietnam Journal of Marine Science and Technology, 2017)
An earthquake has occurred at 10:22:33 UT on 5 August 2014 in the Klerksdorp district, the North West province of South Africa. Its hypocenter is located beneath an Orkney town, where more than 10 gold mines exist. The Council for Geoscience (CGS) in South Africa reported that the magnitude and depth was ML5.5 and 4.7 km, respectively. CGS has been operating 17 surface seismic acceleration stations with 10 km interval in average, and obtained continuous acceleration seismograms through the time of the earthquake and following aftershocks. Using these seismograms, we analyzed the mainshock rupture process of this earthquake. Analyzing these seismograms, we found the ‘initial rupture’ with a Richter scale approximately 4 has occurred 0.3 sec before mainshock. Furthermore, by applying detailed aftershock distribution analysis, we found most of aftershocks occurred surrounding upper and southern part of mainshock rupture area, including initial rupture hypocenter. In order to understand detailed rupture process of this event, we surveyed for strong motion generating area (SMGA) of mainshock by applying Isochrones backprojection method (IBM) to the mainshock S wave waveforms. SMGA distribution seems to fill the vacant space of the aftershock distribution and initial rupture’s hypocenter. And we also found that a horizontal layered seismic vacancy exists between aftershocks with gold mine blastings. This fact implies mainshock rupture did not extent up to gold mine.